Pendampingan Anak Usia dini melalui Edukasi Pelestarian Lingkungan di Gampong Pulo Rungkom Kecamatan Dewantara, Kabupaten Aceh Utara - Rahman, Dahlan A.; Zulhilmi, Zulhilmi; Abubakar, Muhammad Bin; Rizwan, M.; Mulyadi, Mulyadi; Abdullah, Taufik (Jurnal Solusi Masyarakat (JSM), 2025)
The environment is very important for us humans because it has a great impact on life. The lack of knowledge about the environment has led to rampant damage and pollution, including deforation. This has an impact on natural disasters such as eruptions, landslides, floods and other disasters that have an impact on casualties. Therefore, assistance needs to be carried out in an effort to educate the community, starting from children at an early age. Of course, this aspect is carried out in providing knowledge to the community about the impact of environmental damage so that it must be anticipated early. Assistance in early childhood in providing learning about environmental management can have a very important impact in preventing disasters. Therefore, the community must have awareness in implementing environmental conservation patterns by not littering and also polluting the environment. So this community service is carried out to foster public awareness to love the environment and preserve it so that it makes the living environment clean and healthy and beneficial for the community in Pulo Rungkom. Of course, this activity is expected to be useful and a good response from the community in Polo Rungkom village, Dewantara District, North Aceh Regency and can become a pilot as an area whose environment is clean and sustainable nationally.